ANALYSIS OF MANAGEMENT SYSTEMS IN MAINTENANCE OF FACILITIES AND INFRASTRUCTURE AT HEALTH CENTER SABEE KEC. KRUENG SABEE KAB. ACEH WORKS IN 2023 - Erwanita, Erwanita; Kala, Pasyamei Rembune; Hidayattullah, Mhm. (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
This research aims to determine the role of UKGS in improving dental and oral hygiene in elementary school students aged 7 to 9 years at SDN 2 Calang and MIS Cendikia Panton Makmur, Krueng Sabee District, Aceh Jaya Regency. This study is a quantitative descriptive research. The population in this study consisted of 339 elementary school students from SDN 2 Calang and MIS Cendikia Panton Makmur. The research sample was selected using a purposive random sampling technique, comprising 84 students aged 7 to 9 years. Data collection techniques included both primary and secondary data. The research instrument involved examining children's dental plaque using the PHP-M index, and the data were analyzed using chi-square analysis. The study found that schools with UKGS had 93% of students with good dental hygiene, compared to 64.3% in schools without UKGS. Chi-square analysis indicated a significant difference (p = 0.003), confirming the influence of UKGS on dental and oral hygiene. In conclusion, the School Dental Health Program (UKGS) positively impacts dental and oral hygiene among elementary school children, with better outcomes in schools implementing the program.